Devonian smooth-walled tasmanids and new insights of life-cycle descriptions through fluorescence microscopy - Meehan, Kimberly C. (Phytotaxa, 2022)
Fossil microspherules suspected to be marine algal cysts of varying mineralogy are abundant in Paleozoic deposits worldwide. Positive identification of remineralized microspherule fossils is problematic and long debated, particularly for tasmanid species. Several hundred silica-rich microspherules were retrieved through complete maceration of black shale samples from the Givetian Oatka Creek Formation of the Appalachian Basin. Microspherules were analyzed visually through transmitted, incident light, and fluorescence microscopy. The structural features of these microspherules are evident and are interpreted to be Tasmanites sinuous. The images presented herein are the first fluorescence images showing in detail the life cycle stages of the genus Tasmanites. This work also confirms that this tasmanid species does extend into the Givetian as suspected from prior research.